Interactions Between Secondhand Smoke and Genes That Affect Cystic Fibrosis Lung Disease - Collaco, J. Michael (2008)
CONTEXT: Disease variation can be substantial even in conditions with a single gene etiology such as cystic fibrosis (CF). Simultaneously studying the effects of genes and environment may provide insight into the causes of variation. OBJECTIVE: To determine whether secondhand smoke exposure is associated with lung function and other outcomes in individuals with CF, whether socioeconomic status affects the relationship between secondhand smoke exposure and lung disease severity, and whether specific gene-environment interactions influence the effect of secondhand smoke exposure on lung function. DESIGN, SETTING, AND PARTICIPANTS: Retrospective assessment of lung function, stratified by environmental and genetic factors. Data were collected by the US Cystic Fibrosis Twin and Sibling Study with missing data supplemented by the Cystic Fibrosis Foundation Data Registry. All participants were diagnosed with CF, were recruited between October 2000 and October 2006, and were primarily from the United States. MAIN OUTCOME MEASURES: Disease-specific cross-sectional and longitudinal measures of lung function. RESULTS: Of 812 participants with data on secondhand smoke in the home, 188 (23.2%) were exposed. Of 780 participants with data on active maternal smoking during gestation, 129 (16.5%) were exposed. Secondhand smoke exposure in the home was associated with significantly lower cross-sectional (9.8 percentile point decrease; P<.001) and longitudinal lung function (6.1 percentile point decrease; P=.007) compared with those not exposed. Regression analysis demonstrated that socioeconomic status did not confound the adverse effect of secondhand smoke exposure on lung function. Interaction between gene variants and secondhand smoke exposure resulted in significant percentile point decreases in lung function, namely in CFTR non-ΔF508 homozygotes (12.8 percentile point decrease; P=.001), TGFβ1-509 TT homozygotes (22.7 percentile point decrease; P=.006), and TGFβ1 codon 10 CC homozygotes (20.3 percentile point decrease; P=.005). CONCLUSIONS: Any exposure to secondhand smoke adversely affects both cross-sectional and longitudinal measures of lung function in individuals with CF. Variations in the gene that causes CF (CFTR) and a CF-modifier gene (TGFβ1) amplify the negative effects of secondhand smoke exposure.